Crime and Mental Wellbeing - Francesca Cornaglia; Naomi E. Feldman; Andrew Leigh (Institute for the Study of Labor (IZA), 2014)
We provide empirical evidence of crime's impact on the mental wellbeing of both victims and non-victims. We differentiate between the direct impact to victims and the indirect impact to society due to the fear of crime. The results show a decrease in mental wellbeing after violent crime victimization and that the violent crime rate has a negative impact on mental wellbeing of non-victims. Property crime victimization and property crime rates show no such comparable impact. Finally, we estimate that society-wide compensation due to increasing the crime rate by one victim is about 80 times more than the direct impact on the victim.
Keywords: I31; R28; 330; crime; mental wellbeing; neighbourhood effects; non-victims